Frozen "buko" puree utilization and storage studies - Mateo, Mary Jane Chua
This study was aimed at determining the storage life and the acceptability of frozen "buko" puree as an ingredient in food products. The acceptability of the existing formulation for the production of "buko" puree was verified. Physico-chemical tests, microbiological examination and sensory evaluation were done for this purpose and the values obtained were compared with existing standards. It was confirmed that the existing formulation was indeed acceptable. Storage study was carried out for three months at a temperature of -10°C. Changes were monitored and results revealed that the puree can retain its initial qualities after storage for three months at -10°C. Its utilization ingredient in two food products namely: "buko" chicken soup and "buko" cream filling was also evaluated. Sensory results showed that both products produced using the puree were highly acceptable.